Differential degradation of polycyclic aromatic hydrocarbon mixtures by indigenous microbial assemblages in soil. (24th June 2015) - Sawulski, P.; Boots, B.; Clipson, N.; Doyle, E.
Abstract Environmental contamination by polycyclic aromatic hydrocarbons (PAHs) typically occurs as mixtures of compounds. In this study, the response of indigenous soil bacterial and fungal communities to mixtures containing phenanthrene, fluoranthene and benzo(a)pyrene in various combinations was examined using molecular fingerprinting techniques and quantification of a key PAH degradative gene. Results were compared to a parallel study by Sawulski et al. (2014) which examined the effect of these PAHs on soil microbial communities when added as single contaminants. The rate of degradation of individual PAHs varied depending on whether the PAH was present as a single contaminant or in a mixture; phenanthrene was degraded most rapidly when present as a sole contaminant, fluoranthene was removed faster in the presence of the lower molecular weight phenanthrene and the rate of benzo(a)pyrene degradation was reduced in the presence of the 4‐ring PAH, fluoranthene. Bacterial and fungal assemblages differed significantly between treatments regardless of which PAH was added to soil. Although less abundant than the Gram‐negative PAH‐RHDα gene, the gene associated with Gram‐positive bacteria responded to a greater extent to the presence of PAHs, either as single compounds or as mixtures and this increase was significantly correlated with PAH degradation. Significance and Impact of the Study Contaminated sites generally contain complex mixtures of pollutants. Development of effective bioremediation strategies for contaminated soils requires knowledge of the response of soil microbial communities to such mixtures. This study provides information on the degradation of different mixtures of three priority pollutants in soil with a history of polycyclic aromatic hydrocarbon contamination and examines the response of soil bacterial and fungal communities to the presence of these pollutants as sole contaminants or as part of a mixture. This is one of few studies to‐date to compare the effects of single compounds and pollutant mixtures on more than one soil microbial community.